(untitled) (Simbiótica. Revista Eletrônica, 2024)
This essay aims to hear, among the many melodic voices that talk to each other in the field of social science methodology, two of those that seemed to sound most discernible, in light of the Brazilian sociopolitical context of recent years: Gadamerian hermeneutics and critical realism. Arguing that there are margins for thinking about truth, in the philosophy of Hans-Georg Gadamer, as a condition for the emancipation proposed by the realist philosophy of Roy Bhaskar, it presents four sections: the first, which recalls the context in which the philosophies of Gadamer and Bhaskar sounded like the possibility of talking to each other; the second and third, in which its general aspects are addressed, with emphasis on the notions of truth, in Gadamer, and emancipation, in Bhaskar’s explanatory criticism; and, finally, the fourth section, which presents some of the points of convergence between them, from which a “contrapuntal essay” seems to emerge as possible.